Groundbreaking for the Evans Road Building (Institutional Knowledge at Singapore Management University, 2000)
Left to right: Associate Professor Leong Kwong Sin, Deputy President Tan Teck Meng and Associate Professor Low Aik Meng at the Evans Road building groundbreaking ceremony on 12 January 2000. Singapore Management University operated out of the Evans Road building for the first academic year.